Use of 18F-FDG PET in assessing response to treatment in adults with pulmonary sarcoidosis: A systematic literature review - Vij, Oliver; Krishnakumar, Mathangi; Elwell, Helen; Dey, Mrinalini; Kouranloo, Koushan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Symptoms, severity and response to treatment of sarcoidosis can follow a heterogenous pattern, presenting a clinical challenge. Use of Fludeoxyglucose F18 Positron Emission Tomography (18F-FDG PET) in disease monitoring remains uncertain. We undertook a systematic literature review on the use of 18F-FDG PET in assessing response to treatment in adults with pulmonary sarcoidosis. Methods: Articles discussing 18F-FDG PET use in response to treatment in pulmonary sarcoidosis published until January 2024 were included. All article types were eligible except opinion pieces, case reports, case series of ≤10 patients and reviews. Results: Time between baseline 18F-FDG PET and follow-up scan ranged from 2 to 6 months. Compared to clinical response, sensitivity of 18F-FDG PET in determining response to treatment ranged from 56% to 100%, with mean sensitivity of 75.3% (SD 16.0). Conclusions: 18F-FDG PET could be considered in monitoring response to immunosuppression in patients with pulmonary sarcoidosis.